Raman spectroscopy and the search for life signatures in the ExoMars Mission*. Issue 4 (October 2012) - Edwards, Howell G.M.; Hutchinson, Ian B.; Ingley, Richard
Abstract The survival strategies of extremophilic organisms in terrestrially stressed locations and habitats are critically dependent on the production of protective chemicals in response to desiccation, low wavelength radiation insolation, temperature and the availability of nutrients. The adaptation of life to these harsh prevailing conditions involves the control of the substratal geology; the interaction between the rock and the organisms is critical and the biological modification of the geological matrix plays a very significant role in the overall survival strategy. Identification of these biological and biogeological chemical molecular signatures in the geological record is necessary for the recognition of the presence of extinct or extant life in terrestrial and extraterrestrial scenarios. Raman spectroscopic techniques have been identified as valuable instrumentation for the detection of life extra-terrestrially because of the use of non-invasive laser-based excitation of organic and inorganic molecules, and molecular ions with high discrimination characteristics; the interactions effected between biological organisms and their environments are detectable through the molecular entities produced at the interfaces, for which the vibrational spectroscopic band signatures are unique. A very important attribute of Raman spectroscopy is the acquisition of molecular experimental data non-destructively without the need for chemical or mechanical pre-treatment of the specimen; this has been a major factor in the proposal for the adoption of Raman instrumentation on robotic landers and rovers for planetary exploration, particularly for the forthcoming European Space Agency (ESA)/National Aeronautics and Space Administration (NASA) ExoMars mission. In this paper, the merits of using Raman spectroscopy for the recognition of key molecular biosignatures from several terrestrial extremophile specimens will be illustrated. The data and specimens used in this presentation have been acquired from Arctic and Antarctic cold deserts and a meteorite crater, from which it will be possible to assess spectral data relevant for the detection of extra-terrestrial extremophilic life signatures.